Can serum homocysteine predict hypertensive disorders of pregnancy?: an evidence from a case control study in a North Indian tertiary health care institution - Pathania, Kushla; Verma, S. K.; Chamotra, Shaina; Chaudhary, Ankit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertensive disorders of pregnancy are a major cause of both maternal and foetal morbidity and mortality. Although pregnancy induced hypertension (PIH) is still regarded as a disease of theories and unknown etiology, elevated homocysteine level has been hypothesized as a key risk factor. Abnormally raised homocysteine has been significantly associated with increased risk of PIH, abruption, intrauterine growth restriction, recurrent pregnancy loss, intrauterine death and prematurity. Methods: The present case control study was conducted among 180 pregnant women (90 cases and 90 controls) in Kamla Nehru State Hospital for Mother and Child, IGMC Shimla, Himachal Pradesh with an objective of ascertaining the role of homocysteine in pregnancy related hypertensive disorders. Socio-demographic, clinical, biochemical including homocysteine level, laboratory and ultrasonographic parameters of all the participants were documented. Results: The mean homocysteine level of cases (18.30±10.81) was significantly higher than the controls (8.70±2.64). About 62.2% cases had abnormally raised homocysteine level (>15 µmol/L), while only 1.1% controls had such level. The odds of a case having abnormally elevated homocysteine level were 146.6 (CI: 19.52-1101) times to that of controls. Eclamptics had the highest homocysteine level followed by preeclamptics and controls. Conclusions: The present study significantly associates the abnormally elevated homocysteine levels with pregnancy related hypertensive ailments and demands much needed robustly designed studies to further explore the phenomenon. A simple intervention like estimating the much neglected homocysteine levels prior to pregnancy can definitely aid in predicting and preventing perinatal outcomes.